Digital marketing impact on tourism destination in Malaysia: the role of social media reviews / Nur Shayla Imani Mathaias Morision ... [et al.] - Mathaias Morision, Nur Shayla Imani; Mohd Darus, Nur Fadiah Izzati; Abdul Aziz, Azdel; Zain, Razlan Adli; Adzmy, Azahar; Abd Patah, Mohd Onn Rashdi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
Malaysia boasts a plethora of picturesque and unspoiled locations that serve as ideal settings for recreational pursuits, while also offering a rich tapestry of cultural diversity that entices visitors to explore the country. Tourists from around the world are captivated by the diverse cultural activities and iconic landmarks that embody the rich heritage and ancient civilizations of Malaysia. Tourism is a multifaceted phenomenon encompassing social, cultural, and economic dimensions, involving the displacement of individuals to foreign countries or destinations beyond their customary surroundings, driven by personal or business/professional motivations. This adaptability is crucial to guarantee customer happiness, safety, and overall enjoyment. Consequently, travellers have increasingly relied upon websites as primary sources for acquiring pertinent information, while also utilizing social media platforms for various purposes. Therefore, this study explored the three main important facets of social media reviews including quality, quantity, and credibility reviews. A total of 140 responses were recorded through a selfadministered questionnaire survey. Findings found a significant effect of the reviews on travellers’ purchase decision. The findings of this research will provide the tourism industry with a deeper comprehension of the influence exerted by social media reviews on their business operations and its importance in influencing travellers’ decisions.